The Effects of a Female Role Model on Academic Performance and Persistence of Women in STEM Courses - Herrmann, Sarah D.; Adelman, Robert Mark; Bodford, Jessica E.; Graudejus, Oliver; Okun, Morris A.; Kwan, Virginia S. Y. (Basic and applied social psychology, 2016)
Women are more likely to leave science, technology, engineering, and mathematics compared to men, in part because they lack similar role models such as peers, teaching assistants, and instructors. We examined the effect of a brief, scalable online intervention that consisted of a letter from a female role model who normalized concerns about belonging, presented time spent on academics as an investment, and exemplified overcoming challenges on academic performance and persistence. The intervention was implemented in introductory psychology (Study 1, N = 258) and chemistry (Study 2, N = 68) courses. Relative to the control group, the intervention group had higher grades and lower failing and withdrawal rates.